Societal perceptions of aquaculture: Combining scoping review and media analysis - Mausam Budhathoki; Sezgin Tunca; Raquel Lopez Martinez; Wenbo Zhang; Saihong Li; Bertrand Le Gallic; Karen Brunsø; Priya Sharma; Piotr Eljasik; Gergo Gyalog; Remigiusz Panicz; David Little (Reviews in Aquaculture, 2024)
Aquaculture has been recognised for achieving multiple United Nations Sustainable Development Goals; its further growth depends on understanding, and responding to, societal perceptions in a broader context. Thus, this study aims to understand societal perceptions of aquaculture through a scoping review and media analysis. A scoping review identified 151 academic studies for inclusion in our five identified research clusters: (1) social acceptability, (2) growth and development, (3) media coverage, (4) sustainable aquaculture, and (5) consumer perceptions. Further, newspaper articles ( n = 100) were sampled from the United Kingdom, Denmark, France, Spain, Turkey, and China; elsewhere all articles identified were included (Poland, 79; Hungary, 29; India, 70). The findings suggest that scientific and newspaper articles tend to present sustainability aspects in a simplified form. Key stakeholder groups include fish farming enterprises, civil society, governmental officials, scientists, and business leaders both within aquaculture value chains (retailers/wholesalers, technology industry) and outside of them (fisheries, tourism). Also, other stakeholders included the public (indigenous groups, residents, consumers). The stakeholder groups perceived aquaculture differently and depending on the circumstances and context, their perceptions ranged from positive to negative. Many factors influenced their perceptions, including aquaculture's impact on multiple sustainability dimensions, knowledge, transparency, personal interests, types, and location of aquaculture practises, regulations, experience, and sociodemographic characteristics such as age, gender, education, and income. We recommend that aquaculture practitioners focus on context‐specific multifaceted strategies—prioritising transparency, communication, and accountability—and provide essential knowledge to ensure that societal perceptions of aquaculture are based on accurate, empirical information.